Laminar burning velocities of Ethanol-air mixtures at elevated temperatures using the tube method (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Abstract— Experiment test for premixed laminarcombustion of ethanol-air mixtures has been conducted in a tube technique. The laminar burning velocities of premixedhomogeneous Ethanol fuel and air mixtures are determinedover a wide range of equivalence ratio at elevatedtemperatures. The experimental apparatus has beenmodified for apprehension of flame behaviors at 340 K withboth ends open to the atmosphere. For each of the flamespeeds, unburned gas velocities and flame surface areashave been measured and computed to determine burningvelocity. Repeatable and reliable experimental data areobtained in this rig, showing good agreements with previousdata. Laminar burning velocities are increased with elevatedtemperatures.